KATEKESE EKOLOGI KEPADA MASYARAKAT ADAT SEBAGAI TANGGAPAN ATAS ENSIKLIK LAUDATO SI’ - Martinus, Martinus; Gregorius Tinenti, Hemma; Bunga, Jimiana; Nobel Cory Nirwana, Teresa (Amare, 2024)
Community service activities are carried out by prioritizing the spirit of protecting the environment. The equivalent is stated in the Laudato Si' document issued by Pope Francis. This ecological catechesis invites people to be more aware and active in caring for the environment, especially the protected forests around the village. In the catechesis process carried out in Sungai Langer hamlet - Sanggau Regency - West Kalimantan, the service team educated them on the importance of nature and forests, and that it is the responsibility of all village residents to maintain their preservation. This service method is carried out by providing teaching and education through eco-technical catechesis activities to all village residents in accordance with the call of Laudato Si'. The aim of this activity is that people become more sensitive to environmental damage and its impact on human life.